Análise de populações estelares e subestruturas em aglomerados de galáxias - Soares, Natthan Ruschel (2015)
In this work, we investigated differences between stellar populations of galaxies that are part of a cluster with and without substructures. We used optical spectra obtained from Sloan Digital Sky Servey III DR10 for the galaxies of a sample of 1052 clusters selected from Wen et al. (2012) and Tempel et al. (2012) catalogues. For the Wen et al. (2012) catalog, we excluded interlopers by applying the method Shifting gapper to the coordinates and redshifts of all extended sources inside 5 Mpc of radial distance to the center of each system. In order to detect substructure and to estimate the velocity dispersion of individual structures, we used the LocKE algorithm. The individual systems inside clusters with substructure have been classified between primary and secondary, according to their mass dominance. We used the stellar populations synthesis program starlight from Cid Fernandes et al. (2005) to characterize the stellar populations of the galaxies in each structure, and we compared the average results obtained for different types of structure. Substructures have been found in 44% of our sample. The average masses of individual structures, estimated by virial analysis, is 4.5×1014M⊙. The mean stellar age and the mean metallicity obtained for the galaxies is 8.7 ± 2.0×109 years and Z=0.023 ± 0.009, respectively. The mean stellar age distribution for the clusters without substructure, and the primary and secondary structures, show some significant differences. Investigating the stellar populations according to the galaxy luminosity, we found that, in any type of structure, the mean stellar age grows with luminosity, while the fraction of galaxies with mean stellar age less than 6×109 years, decreases. For clusters without substructures, primary and secondary with less mass than 1014.5M⊙, the mean stellar age and luminosity do not show significant differences; however, in massive structures, the mean stellar age increases in the order secondary-primary-without substructure, while the fraction of galaxies with mean stellar age less than 6×109 years decreases. This result suggests that, although the main parameter that affects the stellar age of a galaxy is its mass, the environment also play a significant role, particularly in massive systems.